2016
DOI: 10.3892/or.2016.4714
|View full text |Cite
|
Sign up to set email alerts
|

mir-1-mediated paracrine effect of cancer-associated fibroblasts on lung cancer cell proliferation and chemoresistance

Abstract: Lung cancer is the leading cause of cancer-related mortality in humans worldwide. Moreover, the overall 5-year survival rate is only 15%. Pathologically almost 80% of all lung cancer cases are non-small cell lung cancer (NSCLC). Cancer-associated fibroblasts (CAFs) have been found to exist in a large number of NSCLCs. CAFs have been proven to promote tumor progression, metastasis and resistance to therapy through paracrine effects in most solid tumors. In the present study, firstly we isolated CAFs from patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 17 publications
0
48
1
Order By: Relevance
“…Additionally, Nasser et al () showed that miR‐1 could enhance sensitivity of lung cancer cells to potent anticancer drug doxorubicin. Li et al () also suggested that miR‐1 enhanced DDP sensitivity of cancer‐associated fibroblasts by targeting stromal cell derived factor 1 in lung cancer cells.…”
Section: Introductionmentioning
confidence: 98%
“…Additionally, Nasser et al () showed that miR‐1 could enhance sensitivity of lung cancer cells to potent anticancer drug doxorubicin. Li et al () also suggested that miR‐1 enhanced DDP sensitivity of cancer‐associated fibroblasts by targeting stromal cell derived factor 1 in lung cancer cells.…”
Section: Introductionmentioning
confidence: 98%
“…The low expression of miR-1 induced CAFs causes high secretion levels of SDF-1α. Meanwhile, SDF-1α facilitates lung cancer cell proliferation and cisplatin resistance via CXCR4-activated NF-κB and Bcl-xL [78]. MicroR-27a/b over-expressed in CAFs can alter esophageal cancer cell sensitivity to cisplatin by increasing TGF-β release [59].…”
Section: Introductionmentioning
confidence: 99%
“…Low expression of miR-1 is found in induced CAFs that secrete high levels of SDF-1α. Further studies found that SDF-1α promotes lung cancer cell proliferation and cisplatin resistance via CXCR4-activated NF-κB and Bcl-xL [78]. Similarly, miR-205 is the most down-regulated miRNA in prostate cancer cells as a result of CAF stimulation; miR-205 restitution reduces IL-6 secretion by cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…J. Li, et al show that CAFs from lung cancer patient promoted lung cancer cell resistant to cisplatin in a paracrine manner. High amount of SDF-1 is detected in CAFs which facilitated drug resistance and miR-1 was confirmed negatively regulated the expression level of SDF-1 in the CAFs 68.…”
Section: Role Of Mirnas In Cafs Conducted Chemoresistancementioning
confidence: 84%